409 PROGNOSTIC VALUE OF TENTING AREA ASSESSED BY CMR IN PATIENTS WITH ISCHEMIC MITRAL REGURGITATION. (15th December 2022) - Trimarchi, Giancarlo; Di Bella, Gianluca; Pizzino, Fausto; Donato Aquaro, Giovanni; Luppino, Giovanni; Manganaro, Roberta; Petersen, Christina; Zito, Concetta; Carerj, Scipione; Pingitore, Alessandro
Abstract: Objectives: Mitral regurgitation (MR) due to complications of coronary artery disease is defined as ischemic mitral regurgitation (IMR) and, in the chronic phase after myocardial infarction (MI), it has a negative prognostic value, independently of baseline patient characteristics and degree of left ventricular (LV) dysfunction. In this context, we aimed to determine the additive prognostic role of morphological parameters, assessed by cardiac magnetic resonance (CMR), in patients with ischemic mitral regurgitation (IMR). Methods: 250 patients were recruited with diagnosis of IMR, and they were divided into two groups: those with cardiac death (or appropriate ICD shocks) event at 10 years follow-up (35 patients) and those without cardiac death event (215 patients). All patients underwent CMR imaging for the assessment of left ventricular (LV) ejection fraction (EF), end-diastolic (EDV) and end-systolic volume (ESV), tenting area, tenting height, interpapillary muscles displacement and late gadolinium enhancement (LGE). Echocardiography was performed to assess MR. Results: The average age of the entire sample is 64±10 years, with no significant differences between the two groups (63.2 ±10 vs 68 ±9). For what regards the echocardiographic parameters, there are no statistically significant differences in LVEDV, LVESV, SIV and PP; whereas telesystolic diameter (52 ±7 vs 42 ±9; p < 0, 0001), telediastolic diameter (61 ±4 vs 56 ±7; p = 0, 003), the EROA (0.3 ±0.09 vs 0.25 ±0.6; p < 0, 0001) and left atrial volume (46±19 ml/m 2 vs 38.7±11ml/m 2 p= 0, 0001) are greater in the event group. According to MRI data, patients in the event group, have significantly higher values of LVEDV (155 ±38 ml/m 2 vs 111.09 ±38 ml/m 2; p<0, 001), LVESV (114.04 ±36.8 ml/m 2 vs 70 ± 38; p<0, 001), sphericity index (0.53 ±0.2 vs 0.44 ±0.1; p<0, 001), WMSI (2 ±0.3 vs 1.75 ±0.61, p=0, 02), interpapillary distance (20 ±4 vs 18.4 ±6; p<0, 001) and posteromedial papillary muscle LGE (33% vs 16%; 0, 03). Also, LVEF (28.2 ±9.03% vs 40.42 ±14.9%; p<0, 001) is more impaired in the cardiac death event group. There is statistically significant difference between the two groups for what concerns the tenting area (3.7 ±1.4 cm 2 vs 2.6 ±0.8cm 2 ; p<0, 001) and the tenting height (13 ±2.3 vs 10.5 ±2.6; p<0, 001) which are higher in patients with cardiac death event. In the univariate analysis, parameters that were significantly associated with a worst prognosis are: the severe extent of mitral regurgitation (HR 4, 886; 95% CI 2, 198-10, 861), the tenting area (HR 1, 009; 95% CI 1, 006-1, 013), the tenting height (HR 1, 295; 95% CI 1, 131-1, 482; p<0.05), the PISA radius (HR 1, 329; 95% CI 1, 083-1, 631; p<0.05) the EROA (HR 511, 636; 95% CI 6, 932-37763, 8; p<0.05), LGE PAP PM (HR 2, 169; 95% CI 1, 025-4, 589; p<0.05) and VTDi (HR 1, 012; 95% CI 1, 005-1, 018; p<0.05). In the multivariate analysis it appears that tenting area is an independent predictor (HR 1.009 IC (1.00–1.016) p<0.05) of negative prognosis. Conclusions: Increased tenting area, assessed by CMR, has independent negative prognostic value in patients with ischemic mitral regurgitation. This finding suggests that local remodeling, which occurs in ischemic cardiomyopathy, influences the severity and the prognosis of IMR, underscoring that anatomical compromission has a preeminent role in influencing outcomes in these patients, better than functional parameters.